2018
DOI: 10.1158/1078-0432.ccr-18-1472
|View full text |Cite
|
Sign up to set email alerts
|

Germline and Somatic DNA Damage Repair Gene Mutations and Overall Survival in Metastatic Pancreatic Adenocarcinoma Patients Treated with FOLFIRINOX

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer with lack of predictive biomarkers. We conducted a study to assess DNA damage repair (DDR) gene mutations as a predictive biomarker in PDAC patients treated with FOLFIRINOX. Indiana University Simon Cancer Center pancreatic cancer database was used to identify patients with metastatic PDAC, treated with FOLFIRINOX and had tissue available for DNA sequencing. Baseline demographic, clinical, and pathologic information was gathered. DNA isolation and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 36 publications
(40 reference statements)
1
45
0
1
Order By: Relevance
“…This has been investigated more recently with identification of somatic mutations at varying rates in pancreatic cancer specimen across different studies, ranging from as low as about 4% in an earlier study by Chantrill, et al [93] to over 35% in a sample of 109 micro-dissected pancreatic cancer cases which identified multiple Fanconi anemia genes, ATM, CHEK2, BCLAF1, BRCA1, BRCA2 [94]. The benefit of treatment with platinum agents in these tumors has been comparable to those with germline DDR gene mutations in small retrospective and prospective series [73,75].…”
Section: Discussionmentioning
confidence: 98%
“…This has been investigated more recently with identification of somatic mutations at varying rates in pancreatic cancer specimen across different studies, ranging from as low as about 4% in an earlier study by Chantrill, et al [93] to over 35% in a sample of 109 micro-dissected pancreatic cancer cases which identified multiple Fanconi anemia genes, ATM, CHEK2, BCLAF1, BRCA1, BRCA2 [94]. The benefit of treatment with platinum agents in these tumors has been comparable to those with germline DDR gene mutations in small retrospective and prospective series [73,75].…”
Section: Discussionmentioning
confidence: 98%
“…In the western cohorts, the OS of patients carried with BRCA1/2 or PALB2 mutation was prolonged compared to that of non-carriers (21.8 months DDR mut vs 8.1 months DDR wt) [28]. However, some studies showed that there was no prognostic difference between the two groups, and others even suggested that germline BRCA mutation may induce worse prognosis [29]. No signi cant difference in OS was observed between the patients with or without DDR mutations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to insu cient knowledge about the intricate regulation mechanism of the DDR pathways, current research concerning PDAC used unrecognized standards to classify the DDR genes. For example, some studies de ned 14 or 16 genes as the members of the DDR system [29,36]. Patients in this study pro led using three different gene panels, which had speci c probes covering a different range of gene sets.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers that arise in individuals with a germline mutation in BRCA1/2 , frequently acquire a somatic loss-of-function aberration in the corresponding wild-type BRCA allele, leading to HR repair deficiency. In addition to BRCA1 and 2 mutations, aberrations in other genes (incl PALB2 [85,86], BRCAness [40] and/or high extent of structural rearrangement [5], may lead to loss of functional HR, and importantly, may sensitise these cancers to specific DNA-damaging treatments, including poly(ADP-ribose) polymerase (PARP) inhibitors and DNA-intercalating agents (mitomycin C, platinum-based combinations).…”
Section: The “Omic” Diversity Of Pdacmentioning
confidence: 99%
“…With growing evidence supporting the clinical development of PARP- or platinum-based regimens (including FOLFIRINOX [85]) in the treatment of BRCA -mutated PDAC, the National Comprehensive Cancer Network (NCCN) has recommended consideration of a first-line platinum-based regimen in patients with advanced PDAC and a hereditary cancer syndrome involving a DNA repair mutation [96]. Ongoing clinical studies further aim to assess the tolerability and efficacy of PARP-inhibitor based combinations regimens (NCT01585805), or their utility as maintenance monotherapy after first-line platinum-based chemotherapy in BRCA1 , BRCA2 or PALB2 -mutant pancreatic cancer (NCT02184195, NCT03140670).…”
Section: The “Omic” Diversity Of Pdacmentioning
confidence: 99%